Experiences of disabled students at two South African universities: a capabilities approach - Mutanga, Oliver (University of the Free State, 2015)
𝑬𝒏𝒈𝒍𝒊𝒔𝒉 Using the capabilities approach, this thesis examines how disabled students experience higher education at two South African universities: University of the Free State (UFS) and University of Venda (UniVen). Located within the equity and inclusive agenda, the study seeks to exert influence over higher education policies and practices. South Africa prioritises equity issues. It is among the few countries in the world (156 as of 2015) to have signed and ratified one of the most acclaimed conventions on disability, the 2008 Convention on the Rights of Persons with Disabilities (CRPD). However, there is no legislation (in 2015) that specifically looks at disability issues in South African higher education (SAHE) and data on disabled students is thin. I argue that the capabilities approach is important in framing our understanding of disability issues in higher education. It also provides an analytical framework to measure progress towards social justice. The capabilities approach acknowledges the interplay between individual bodies and various conversion factors in the concept and construction of disabilities. This thesis advances knowledge in higher education and disability disciplines by outlining the complexities in disabled students’ lives at the two universities. This study sought to answer the following questions. 1. How do disabled students experience their studies and interact with higher education? 2. How do lecturers and Disability Unit staff understand disability and the experiences of disabled students? 3. What are the differences and similarities concerning university policies and other supporting arrangements for disabled students at the University of the Free State and University of Venda? 4. How does the capabilities approach account for the experiences of disabled students in higher education? 5. What implications can be drawn for disability policy to enhance social justice in higher education? As a result of the historical trajectories that still influence the present-day state of SAHE, two universities with different historical and cultural backgrounds were selected. UFS is a historically-advantaged urban-based white Afrikaans university. It has gone through the processes of major transformation in recent years. By contrast, UniVen is a historically-disadvantaged rural-based university. It was established under apartheid policy to serve the African black community. Officially, it reports the highest number of disabled students in SAHE. Purposive sampling was employed to recruit participants into the study. Participants included fourteen disabled students from various disability categories, four lecturers and three Disability Unit (DU) staff. Students were recruited from the DU by telephone after being provided with a list of registered disabled students. The DU staff were approached directly and recruited to the study. Lecturers were recruited through their respective Heads of Departments. An information sheet was provided to every participant; this was accompanied by a conversation with each participant before they signed the consent form. Data in this qualitative study were collected through in-depth interviews, field observations and institutional document analysis. In-depth interviews with disabled students, lecturers and the DU staff focused on their experiences with disability issues and their perceptions of the needs of disabled students. Field observations were also incorporated into the study in order to expand my understanding of the experiences of disabled students at the two universities. In order to get a comprehensive understanding of relevant issues, I spent a day with one participant at each university, in their setting from residence to the classes. I was able to determine how the students interact with their peers, what happens in classrooms and in their places of residence. Furthermore, some university policy documents (e.g. disability policies, assessment policies and residence policies) were reviewed in order to understand how the two higher education institutions (HEIs) purport to address issues and then the results of the review were juxtaposed with what was gathered from the other mentioned data collection methods. Data were analysed thematically with the help of NVivo software and five key findings emerged from the students’ data. Findings from this study highlight the complexities around the adoption of an identity as a disabled person by these students. Understanding disability within a given social and cultural context is important, as interpretations of what is disability are influenced by context. The study also found that, as a result of the current thinking around disability, some practices and non-actions in higher education perpetuate injustices towards disabled students, although their intended goals are to create opportunities for all students. Another finding from the study is that, in most cases, the challenges faced by disabled students in higher education are not the same and they respond to these challenges differently. It was further found that regardless of these challenges, disabled students have the capacity to aspire and they showed educational resilience. The last finding from the students highlights that disabled students, just like other students, know what they value in higher education. Participating students identified key valued freedoms and opportunities that are needed to access and succeed in higher education. Eleven key valued freedoms and opportunities were extrapolated, and I argue that these are needed for the formulation of socially just disability-inclusive policies. Interviews with university staff show a lack of awareness among lecturers on disability matters due to lack of training and at times this is compounded by their socio-cultural backgrounds and job expectations from their universities. On the other hand, DU staff showed an appreciation of disability matters. However, their efforts at times are compromised by arrangements within the university linked to lack of national and university policy guidelines. The thesis ends by suggesting some key points for SAHE to consider for an inclusive-disability policy framework.

𝑨𝒇𝒓𝒊𝒌𝒂𝒂𝒏𝒔 Deur die gebruik van die vermoëns-perspektief, ondersoek hierdie tesis hoe gestremde studente hoër onderwys ervaar aan twee Suid-Afrikaanse universiteite, die Universiteit van die Vrystaat (UV) en die Universiteit van Venda (UniVen). Gesitueer binne ŉ agenda van gelykheid en inklusiwiteit, poog hierdie studie om hoër onderwys beleide en handelinge te beïnvloed. Suid-Afrika prioritiseer sosiale gelykheid en is een van min lande in die wêreld (156 teen 2015) wat een van die mees bekroonde konvensies rakende gestremdheid, die 2008 Konvensie op die Regte van Mense met Gestremdhede, geteken en bekragtig het. Daar is egter geen wetgewing (in 2015) wat spesifiek omsien na kwessies rakende gestremdhede in Suid-Afrikaanse hoër onderwys (SAHO) nie en data oor gestremde studente is min. Ek stel voor dat die vermoënsbenadering belangrik is om ons begrip van kwessies rakende gestremdhede in hoër onderwys te verdiep. Dit verskaf ook ŉ analitiese raamwerk om vordering na sosiale geregtigheid te meet. Die vermoënsbenadering erken die wisselwerking tussen individuele instellings en verskeie omskakelingsfaktore in die skepping van gestremdhede. Hierdie tesis bevorder kennis in hoër onderwys en dissiplines rakende gestremdheid deur die kompleksiteit van gestremde studente aan twee universiteite se lewens uit te lig. Hierdie studie beoog om die volgende vrae te beantwoord: 1. Hoe ervaar gestremde studente hul studies en hoe lyk die interaksie tussen hulle en hoër onderwys? 2. Hoe verstaan dosente en personeel aan die eenhede vir gestremdheid gestremdhede en die ervaringe van gestremde studente? 3. Wat is die verskille en ooreenkomste tussen universiteitsbeleide en ander ondersteuning vir gestremde studente aan die Universiteit van die Vrystaat en die Universiteit van Venda? 4. Hoe neem die vermoënsbenadering effektief die ervaringe van gestremde studente in hoër onderwys in ag? 5. Watter implikasies kan afgelei word vir ŉ beleid oor gestremdheid om sosiale geregtigheid te bevorder? As gevolg van historiese trajekte wat steeds hedendaagse SAHO beïnvloed, is twee universiteite met verskillende historiese en kulturele agtergronde geselekteer. Die UV is ŉ histories-bevoordeelde, stedelike, voormalige wit, Afrikaanse universiteit wat deur verskeie transformasie prosesse gegaan het die afgelope jare. UniVen is ŉ historiese-benadeelde, plattelandse universiteit wat in die apartheidsjare geopen is om die swart, Afrika gemeenskap te dien. UniVen rapporteer offisieel dat hulle die hoogste aantal gestremde studente in SAHO het. Doelgerigte steekproefneming is gebruik om kandidate vir die studie te selekteer. Die kandidate het bestaan uit veertien gestremde studente uit verskeie kategorieë van gestremdheid, vier dosente en drie personeellede van gestremdheid eenhede. ŉ Lys van geregistreerde gestremde studente is verkry van die eenhede, waarna geselekteerdes telefonies deur die eenhede gekontak is. Die personeel aan die eenhede was direk gekontak om deel te neem aan die studie. Dosente was deur hul onderskeie departementshoofde gekontak. ŉ Inligtingsdokument was aan elke kandidaat gegee en ŉ verbale gesprek is met elke kandidaat uitgevoer voordat toestemmingsvorms geteken is. Data in hierdie kwalitatiewe studie is deur in-diepte onderhoude, veld observasies en institusionele dokument analise gekollekteer. In-diepte onderhoude met gestremde studente, dosente en die eenhede se personeel het gefokus op hul ervaringe met kwessies rakende gestremdhede, asook hul persepsies oor die behoeftes van gestremde studente. Veld observasies was ook ingesluit in die studie om my eie begrip van die ervaringe van gestremde studente aan die twee universiteite aan te help. Om ŉ omvattende begrip van kwessies te kry, het ek ŉ dag saam met een kandidaat by elke universiteit spandeer, van hul wonings tot klasse. Dit het my in staat gestel om te ervaar hoe die studente met hul medestudente omgaan, asook wat in die klaskamers en wonings gebeur. Sekere universiteitsbeleide (bv. Beleide oor gestremdhede, assessering en behuising) was ook ondersoek om beter begrip te kry van hoe die twee hoër onderwys institute beweer om kwessies aan te spreek. Die resultate van die ondersoek was daarna opgeweeg teenoor data wat deur die ander genoemde metodes ingesamel is. Data is geanaliseer volgens temas met die hulp van NVivo sagteware en vyf sleutelbevindinge wat deur die studente se data na vore gekom het. Die bevindinge van die studie lig kompleksiteite oor die aanneming van ŉ identiteit van ŉ gestremde persoon deur die studente uit. Om gestremdhede binne ŉ gegewe sosiale en kulturele konteks te verstaan is belangrik omdat interpretasies oor wat gestremdheid is, word beïnvloed deur konteks. Die studie het ook gevind dat sekere handelinge en uitgelate handelinge in hoër onderwys ongelykhede bevorder teenoor gestremde studente as gevolg van huidige denke en begrip oor gestremdhede, selfs al is die beoogde doelwitte om geleenthede vir alle studente te skep. Nog ŉ bevinding van die studie is dat in meeste gevalle, die uitdagings wat gestremde studente in hoër onderwys moet oorkom nie dieselfde is nie en hulle respons teenoor die uitdagings ook verskil. Dit is verder gevind dat gestremde studente die kapasiteit het om te streef na doelwitte en opvoedkundige veerkragtigheid toon ten spyte van die uitdagings. Die laaste bevinding van die studente is dat gestremde studente, net soos ander studente weet wat hulle waardevol vind in hoër onderwys. Deelnemende studente het sleutel vryhede en geleenthede geïdentifiseer wat nodig is om toegang te kry tot en sukses te behaal in hoër onderwys. Elf sleutel-gewaardeerde vryhede en gelykhede is geëkstrapoleer en ek stel voor dat hulle nodig is vir die formulering van sosiale geregtelike insluitende beleide vir gestremdhede. Onderhoude met universiteitspersoneel wys ŉ gebrek aan bewustheid onder dosente oor kwessies rakende gestremdhede as gevolg van ŉ gebrek aan opleiding, wat ook soms saamgestel word deur hul sosio-kulturele agtergrond en werksverwagtinge van hul universiteite. Aan die ander kant het personeel aan die eenhede vir gestremdhede waardering vir kwessies rakende gestremdhede, alhoewel hul pogings met tye in gedrang kom deur sekere reëlings binne die universiteit, wat terugverwys kan word na die gebrek aan nasionale en universiteitsbeleide wat riglyne gee. Die tesis sluit af deur sekere voorstelle te maak vir SAHO om in ag te neem vir ŉ insluitende gestremdheidsbeleid raamwerk.
Thesis (Ph.D. (Development Studies))--University of the Free State, 2015
Keywords: Education, Higher -- South Africa; People with disabilities -- Education (Higher) -- South Africa; University of Venda; University of the Free State; Students with disabilities -- South Africa